2018
DOI: 10.5194/acp-18-3779-2018
|View full text |Cite
|
Sign up to set email alerts
|

How a European network may help with estimating methane emissions on the French national scale

Abstract: Abstract. Methane emissions on the national scale in France in 2012 are inferred by assimilating continuous atmospheric mixing ratio measurements from nine stations of the European network ICOS located in France and surrounding countries. To assess the robustness of the fluxes deduced by our inversion system based on an objectified quantification of uncertainties, two complementary inversion set-ups are computed and analysed: (i) a regional run correcting for the spatial distribution of fluxes in France and (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Some studies 86 Here, we present the Bayesian variational inverse system PYVAR-CHIMERE, that has reached a 96 good level of maturity (robustness of calculations, clarity, portability, modularity of the code) and 97 that is adapted to reactive species such as CO and NO2. This adaptation for reactive species takes 98 advantage of the previous developments for the quantification of fluxes of long-lived GHG species 99 such as CO2 [Broquet et al, 2011] and CH4 [Pison et al, 2018] at the regional to the local scales, 100 paving the way for monitoring anthropogenic emissions at high spatial resolutions. The PYVAR-101 CHIMERE inverse modeling system is based on the Bayesian variational assimilation code PYVAR 102 [Chevallier et al 2005] and on the regional state-of-the-art CTM CHIMERE, dedicated to the study 103 As shown in Figure 1, the minimization algorithm repeats the forward-adjoint cycle to seek an optimal 159 solution for the control parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies 86 Here, we present the Bayesian variational inverse system PYVAR-CHIMERE, that has reached a 96 good level of maturity (robustness of calculations, clarity, portability, modularity of the code) and 97 that is adapted to reactive species such as CO and NO2. This adaptation for reactive species takes 98 advantage of the previous developments for the quantification of fluxes of long-lived GHG species 99 such as CO2 [Broquet et al, 2011] and CH4 [Pison et al, 2018] at the regional to the local scales, 100 paving the way for monitoring anthropogenic emissions at high spatial resolutions. The PYVAR-101 CHIMERE inverse modeling system is based on the Bayesian variational assimilation code PYVAR 102 [Chevallier et al 2005] and on the regional state-of-the-art CTM CHIMERE, dedicated to the study 103 As shown in Figure 1, the minimization algorithm repeats the forward-adjoint cycle to seek an optimal 159 solution for the control parameters.…”
mentioning
confidence: 99%
“…382 This paper presents the Bayesian variational inverse system PYVAR-CHIMERE, which has been 383 adapted to the inversion of reactive species such as CO and NO2, taking advantage of the previous 384 developments for long-lived species such as CO2[Broquet et al, 2011] and CH4[Pison et al, 2018]. 385We show the potential of PYVAR-CHIMERE, with inversions for CO and NO2 illustrated over 386Europe for an example day.…”
mentioning
confidence: 99%
“…Top-down approaches have already been undertaken to quantify national surface flux inventories of the main greenhouse gases (CO 2 , CH 4 and N 2 O) via national surface in situ networks as in Peters et al (2007), Ganesan et al (2015) and Henne et al (2016), or pan-national inventories using international greenhouse gas monitoring network databases (e.g. Cressot et al, 2016;Bergamaschi et al, 2015Bergamaschi et al, , 2018Pison et al, 2018). There is also a need for increased coverage in the Southern Hemisphere (Thompson et al, 2014;Wells et al, 2015), which is relatively data sparse compared to the Northern Hemisphere.…”
mentioning
confidence: 99%
“…The original reason for the establishment of greenhouse gas in situ measurements at Lauder were two-fold. First, with the establishment of a TCCON site at Lauder in 2004(Wunch et al, 2011Pollard et al, 2017) it was an initial requirement that sites have co-located continuous high-precision surface in situ measurements of CO 2 and CH 4 . This was to provide a priori surface concentration constraints for the TC-CON total column dry mole fraction retrievals and provide an independent estimate of boundary layer CO 2 and CH 4 .…”
mentioning
confidence: 99%
“…The potential of ICOS continuous measurements of CO2 dry air mole fraction to improve Net Ecosystem Exchange estimates at the mesoscale across Europe has been evaluated in Kadygrov et al (2015). Pison et al (2018) addressed the potential of the actual ICOS European network for the methane emission estimation at the French national scale. 25…”
mentioning
confidence: 99%